The Impact of the 30-Meter Sprint Exercise on Students’ Long Jump Performance Using the Squat Technique - Ilahi, Rahmat Rido; Iyakrus, Iyakrus; Primasari, Dwi Ammelia Galuh (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines the effect of 30-meter sprint exercise on the long jump performance of junior high school students using squat style techniques. Thirty students participating in sports extracurricular activities at SMPN 1 Gelumbang were divided into 2 groups, namely control and experimental groups, with the same number. The experimental group received special treatment in the form of undergoing a 30-meter sprint training program for six weeks, where face-to-face training was carried out three times per week. Pretest-posttest used in collecting data. Then the data was analyzed using normality, homogeneity, and paired sample t-tests. The results showed a statistically significant improvement in long jump performance in the experimental group. Sprint training by students has been shown to improve the repulsion and coordination that are important in squatting styles in long jump athletics.